High stakes, high hopes : urban theorizing in partnership - Oldfield, Sophie (Geographies of justice and social transformation, 2023)
"High Stakes, High Hopes tracks the building of urban theorizing in a partnership between a South African township community organization, grappling with the legacies of (post)apartheid inequality, and a university tasked to research and teach the city. The book reflects on what was at stake in the partnership and its creative, and at times, conflictive, evolution. It explores what changed in learning when teaching and assessment moved in and between the university classroom and township streets and ordinary people's households. It engages ways academic research and assessment were reshaped when framed in neighbourhood questions and commitments, and what was reoriented in urban theorizing when Civic activism and township struggles were recalibrated as sites of valid knowledge-making. In its narrative form, Oldfield builds an embodied argument for collaborative urbanism to engage the city, its substance, its stories, its everyday contradictions, and possibilities. The book offers forms of practice, grounded in teaching, to train a next generation of urbanists to understand and engage the city embedded in multiple publics and politics across the city. It contributes to an archive of alternative kinds of urban knowledges, experiments which work to inspire more varied forms of urban theorizing"--